Advances in Cell Mechanics - Li, Shaofan; Sun, Bohua; SpringerLink (Online service) (2011)
"Advances in Cell Mechanics" presents the latest developments in cell mechanics and biophysics, mainly focusing on interdisciplinary research in cell biology and the biophysics of cells. Moreover, a unique feature of the book is its emphasis on the molecular and complex continuum modeling and simulations of the cells. It may be the first work that brings rigorous and quantitative scientific analysis and state-of-the-art simulation technology into cell biology research. The book is intended for researchers and graduate students working in the fields of molecular cell biology, bio-engineering and bio-mechanics, soft matter physics, computational mechanics, bio-chemistry and bio-medicine. All contributors are leading scholars in their respective fields. Dr. Shaofan Li is a professor and an expert for computational mechanics at the University of California-Berkeley, USA; Dr. Bohua Sun is a professor at Cape Peninsula University of Technology, South Africa.
Modeling and Simulations of the Dynamics of Growing Cell Clusters -- Multiscale Biomechanical Modeling of Stem Cell-Extracellular Matrix Interactions -- Modeling of Proteins and Their Interactions with Solvent -- Structural, Mechanical and Functional Properties of Intermediate Filaments from the Atomistic to the Cellular Scales -- Cytoskeletal Mechanics and Rheology -- On the Application of Multiphasic Theories to the Problem of Cell-substrate Mechanical Interactions -- Effect of Substrate Rigidity on the Growth of Nascent Adhesion Sites -- Opto-Hydrodynamic Trapping for Multiaxial Single-Cell Biomechanics -- Application of Nonlocal Shell Models to Microtubule Buckling in Living Cells.
Keywords: ENGINEERING; BIOPHYSICS AND BIOLOGICAL PHYSICS; COMPUTER SIMULATION; SIMULATION AND MODELING; CELL BIOLOGY; CYTOLOGY; MECHANICS, APPLIED; THEORETICAL AND APPLIED MECHANICS; BIOCHEMICAL ENGINEERING; BIOMATERIALS